2004
DOI: 10.1002/path.1634
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic analysis of human spermatocytic seminomas

Abstract: We performed comparative genomic hybridization (CGH) on 8 formalin-fixed, paraffin wax-embedded primary spermatocytic seminomas (SS) from 7 patients, one of whom developed metastatic disease. In general, this tumour type is not associated with development of metastases. Since there are only few reported cases of metastatic SS in the literature, this study is the first report of chromosomal constitution in a patient with metastatic disease. Chromosomal imbalances were observed in all 8 tumours analysed by CGH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 23 publications
(36 reference statements)
2
20
0
Order By: Relevance
“…Gain of the short arm of chromosome 12 is the consistent finding in seminomas/ dysgerminomas (see refs. 18, 19 for review), whereas additional copies of chromosome 9 has been found in all spermatocytic seminomas studied to date (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Gain of the short arm of chromosome 12 is the consistent finding in seminomas/ dysgerminomas (see refs. 18, 19 for review), whereas additional copies of chromosome 9 has been found in all spermatocytic seminomas studied to date (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…5,7 Spermatocytic seminoma is rare (<1% of germ cell tumors [GCTs]), originates from more mature germ cells compared with classic seminoma, and has entirely different genetic and morphologic signatures. 8,9 These tumors are also unique because cryptorchidism is not a risk factor and they typically present in older men (mean age at diagnosis, 54 years). 10 Microscopy shows 3 distinct cell types (small, medium, and large) with round nuclei and no placental alkaline phosphatase expression.…”
Section: Histologic Subtypesmentioning
confidence: 98%
“…Comparative genomic hybridization and interphase fluorescent in situ hybridization have shown that gain of chromosome 9 is common in spermatocytic seminoma. 8,21 Differential Diagnosis…”
Section: Eblementioning
confidence: 99%
“…Another case has been reported to have metastasized to lymph nodes, but no photomicrographs were published to document the case. 8 Spermatocytic seminoma has been associated with a testicular sarcoma in approximately a dozen cases. Most of these patients have died of metastases within a few months.…”
Section: Clinical Featuresmentioning
confidence: 99%